Tensile Strenght dan Elongation at Break Edible Film Pati Singkong dengan Variasi Bahan Tambahan: Penelitian - Nurgita Shelvi; Selfi Nafita; Nurlin; Rizqi Hidayatullah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of cassava starch-based edible films has gained increasing attention as a biodegradable alternative to conventional plastic food packaging. This review aimed to evaluate the mechanical properties—tensile strength and elongation at break—of cassava starch-based edible films treated with different additive formulations, with particular emphasis on the formulation of whey protein and beeswax. A literature review method was conducted by collecting and analyzing data from recent scientific studies. The primary reference was the study by Cortés-Rodríguez et al. (2020), which utilized a face-centred composite design to test various film formulations. Among the evaluated formulations, whey protein (1.0%) and beeswax (0.25%) demonstrated superior mechanical performance, with a tensile strength of 0.848 ± 0.077 MPa and an elongation at break of 78.9 ± 15.1%. This composition approached the tensile strength achieved by citric acid-based films, while significantly outperforming them in flexibility. The balanced mechanical profile of this formulation ensured sufficient strength to withstand mechanical stress during handling and transportation, as well as adequate flexibility to conform to the shape of packaged food without cracking. In contrast, citric acid-based films had slightly higher tensile strength but much lower elongation (25.0967%), limiting their application in flexible packaging. In conclusion, cassava starch-based edible films incorporating whey protein and beeswax showed an ideal balance of strength and flexibility, making them a promising and sustainable alternative for food packaging applications.